Variable application of fertiliser in permanent pastures - Serrano, João (2012)
Alto Alentejo is a southern province of Portugal with over 200,000ha under permanent pasture. This paper describes the major steps required to accomplish the objective of demonstrating new technology for fertiliser application in permanent pasture. A description of the equipment gathering, methodology followed as well as the results of the first year will be presented.